Characteristics of Children with Newly Diagnosed Type 1 Diabetes Mellitus in Brunei Darussalam - Wee, Chun Yen; Yong, Alice Moi Ling; Chong, Chee Fui; Soon, Ing Shian (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Objective. This study aims to characterize the presentation, biochemical status of children with T1DM at diagnosis, the type of subcutaneous insulin regimens initiated, and to determine the incidence of T1DM in Bruneian children aged 18 years and younger. Methodology. A retrospective electronic and paper medical chart review was performed on patients aged 18 years and younger diagnosed with T1DM from 2013 to 2018 in Brunei Darussalam. Results. A total of 31 children with a mean age of 10.2 ± 3.6 years old were diagnosed with T1DM, of which 66.7% presented with diabetic ketoacidosis (DKA), a majority in severe DKA with an intercurrent illness (p=0.021). The mean HbA1c was 13.6 ± 2.7% with a mean serum glucose of 37.0±14.9 mmol/L at diagnosis. In the majority of the children (67.7%), multiple daily injections of subcutaneous insulin were initiated. The incidence of T1DM in children aged 18 years and younger was 4.9 per 100,000 for the year 2018. Conclusions. The majority of the patients in this study presented with severe DKA with an intercurrent illness. This highlights the importance of childhood T1DM awareness among the public and healthcare providers. The incidence of childhood T1DM in Brunei Darussalam is similar to other countries in the Asian region, being relatively low, compared to the rest of the world.